HUBUNGAN ANTARA WAKTU KERJA DAN KETERLIBATAN AYAH - Gabriella Alika Rayna Soetopo; Wieka Dyah Partasari (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2022)
Paternal involvement is necessary for children ages 6-12 to thrive optimally. On the other hand,fathers face a challenge of having limited time to spend with their children as a result of being abreadwinner to fulfil the family’s needs. This research aimed to identify the relationship betweenthe time fathers spent at work and the paternal involvement of fathers with children ages 6-12years old. This was quantitative research with a correlational design. There were 50 fathers withchildren between the ages of 6-12, currently working, and living in Jabodetabek as participants.Father’s paternal involvement was measured using the Paternal Involvement Questionnaire. Thetime fathers spent working were collected using a time sheet. Participants recorded their dailyactivities within a 30-minute interval for 7 days. The hypothesis was tested using the Spearmancorrelation test which showed that there was no significant relationship between the time fathersspent at work and the paternal involvement of fathers with children ages 6-12 years old. This resultindicated that even if fathers spent more time working, this doesn’t mean they have lower paternalinvolvement than fathers who spent less time working. For future research, it is recommended toinvestigate further the relationship between father involvement, father's location of work, father'sassistance in taking care of children, and maternal gatekeeping.